Effects of Metabolic Syndrome on Semen Quality and Circulating Sex Hormones: A Systematic Review and Meta-Analysis - Zhao, Liming; Pang, Aixia (Frontiers in Endocrinology, 2020)
Previous studies were controversial in the effects of metabolic syndrome (MetS) on semen quality and circulating sex hormones, and thus we conducted a systematic review and meta-analysis to clarify the association. A systematic search was conducted in public databases to identify all relevant studies, and study-specific standardized mean differences (SMD) and 95% confidence intervals (CI) were pooled using a random-effects model. Finally, 11 studies were identified with a total of 1,731 MetS cases and 11,740 controls. Compared with the controls, MetS cases had a statistically significant decrease of sperm total count (SMD: −0.96, 95% CI: −1.58 to −0.31), sperm concentration (SMD: −1.13, 95% CI: −1.85 to −0.41), sperm normal morphology (SMD: −0.61, 95% CI: −1.01 to −0.21), sperm progressive motility (SMD: −0.58, 95% CI: −1.00 to −0.17), sperm vitality (SMD: −0.83, 95% CI: −1.11 to −0.54), circulating follicle-stimulating hormone (SMD: −0.87, 95% CI: −1.53 to −0.21), testosterone (SMD: −5.61, 95% CI: −10.90 to −0.31), and inhibin B (SMD: −2.42, 95% CI: −4.52 to −0.32), and a statistically significant increase of sperm DNA fragmentation (SMD: 0.76, 95% CI: 0.45 to 1.06) and mitochondrial membrane potential (SMD: 0.89, 95% CI: 0.49 to 1.28). No significant difference was found in semen volume, sperm total motility, circulating luteinizing hormone (LH), estradiol, prolactin and anti-Müllerian hormone (AMH) (P > 0.05). In conclusion, this meta-analysis demonstrated the effects of MetS on almost all the semen parameters and part of the circulating sex hormones, and MetS tended to be a risk factor for male infertility. Further larger-scale prospective designed studies were needed to confirm our findings.